C‐type lectin domain family 5, member A (CLEC5A, MDL‐1) promotes brain glioblastoma tumorigenesis by regulating PI3K/Akt signalling. (4th March 2019) - Fan, Hong‐Wei; Ni, Qi; Fan, Ya‐Ni; Ma, Zhi‐Xiang; Li, Ying‐Bin
Abstract: Objectives: Glioblastoma is the most common malignant glioma of all brain tumours. It is difficult to treat because of its poor response to chemotherapy and radiotherapy and high recurrence rate after treatment. The aetiology of glioblastoma is a result of disorders of multiple factors. Depending on cell signal transduction, these glioblastoma‐associated factors lead to cell proliferation, differentiation and apoptosis. Therefore, investigation of the potential factors which involved in the development of glioblastoma could provide a new target for the treatment of glioblastoma. Materials and methods: We analysed the transcript expression of CLEC5A in glioblastoma by accessing The Cancer Genome Atlas (TCGA). qRT‐PCR was performed to detect the RNA expression of genes in cells and tissues, and Western blot was used to measure the protein levels (Cyclin D1, Bcl‐2, BAX, PCNA, MMP2, MMP9, Akt and Akt phosphorylation) in tissues and cells. Cell proliferation, migration, invasion, cycle and apoptosis were measured by CCK‐8, transwell and flow cytometry assays, respectively. Ki67 level and lung metastasis were determined by immunochemistry and H&E staining. Results: In this study, we found that CLEC5A was highly upregulated in glioblastoma compared to normal brain tissues, which had an opposite relation with the overall patient survival. Downregulation of CLEC5A could inhibit cell proliferation, migration and invasion via promoting apoptosis and G1 arrest. In contrast, overexpression of CLEC5A stimulated cell proliferation, migration and invasion. In addition, we found that CLEC5A level was positively correlated with Akt phosphorylation level. Akt inhibitor or agonist could reverse the modulation effects of CLEC5A in glioblastoma. Moreover, In vivo results suggested that inhibition of CLEC5A significantly reduced tumour size, weight, cell proliferation ability and lung metastasis via inhibition of phosphorylation Akt. Conclusion: Both in vitro and in vivo evidences supported that CLEC5A was involved in glioblastoma pathogenesis via regulation of PI3K/Akt pathway. Thus, CLEC5A might serve as a potential therapeutic target in the treatment of glioblastoma in the future.